Guidelines for Applying Metacognitive Strategies and ChatGPT in Teaching Korean Writing - Khoatkham, Kittichon (Manutsat Paritat: Journal of Humanities, 2026)
This article aims to propose guidelines for applying metacognitive strategies and ChatGPT to the teaching of Korean writing, serving as a foundation for classroom implementation and for further research. To this end, the article reviews and synthesizes relevant literature, conceptual frameworks, and theories on language learning strategies, metacognitive strategies, process-oriented writing, and the use of ChatGPT in teaching Korean writing. The synthesis suggests that metacognitive strategies—especially planning, self-monitoring, and self-evaluation—enhance learners’ self-awareness and self-regulation, leading to improved writing performance. These core strategies can also be integrated with ChatGPT, which can support learners quickly through reflective questioning and the provision of hints. Nevertheless, such use should be guided by clear ethical principles, and human teachers remain essential for providing critical feedback and making final evaluations. Based on these findings, the article designs an instructional model grounded in the Cognitive Academic Language Learning Approach (CALLA; O’Malley & Chamot, 1990), consisting of five stages: preparation, presentation, practice, evaluation, and expansion. Process-oriented writing stages are incorporated into the practice phase, and sample prompts as well as a checklist for assessing learners’ use of metacognitive strategies are also provided.